Analysis of E-Learning Activities at SDIT Future Islamic School Pekanbaru (Journal of Primary Education, 2020)
This study aims to describe and analyze e-learning activities at SDIT Future Islamic School (FIS) Pekanbaru. The subject and sample of the research used science teacher class VI and students of SDIT FIS Pekanbaru class VI A and B totaling 30 people. The study is a qualitative research with descriptive approach. The technique used in this study is observation and interviews, while the research instrument used field notes in the form of observations of e-learning activities and free-tied interview sheets. The data of e-learning activities provide from observations were student activities, such as writing, speaking, listening, observing, motoric skills, and mental activities such as activity that requires knowledge construction asking students to interpret, analyze, synthesize, or evaluate information or ideas when answering practice questions. Student activities are series of implementation of e-learning that technology in education. The results of interviews and observations show that the implementation of e-learning model were two modes. They were by using blended models and asynchronous methods in the application of mixing conventional learning (meeting in class) by utilizing technology to display subject matter offline. The implementation of e-learning in this school utilizes computer technology, LCDs, and speakers as a tool to deliver teaching materials to students. The e-learning implementation carried out in the learning process, included use of technology to display learning material, learning information, and also the students work results. The hardware such as laptop, LCD, and loudspeakers used by teachers and students to display information related to decay and weathering topics in the form of videos and pictures on natural science subjects. E-learning activities provide benefits to students and teachers in understanding the concept of subject matter that is packaged by the teacher in an exciting and informative manner.